Pengunaan E-Money di Lingkungan Pesantren Sebagai Bentuk Transformasi Sistem Pembayaran di Era Digital (Studi Kasus Pondok Pesantren Nurul Qarnain) - Halili, Halili (Maisyatuna, 2023)
E-money which has been echoed since August 2014 as a means of transaction now continues to increase in terms of use, this increase proves that e-money has now become a payment instrument that is very popular with many people, including Islamic boarding schools. This study wants to know and analyze the motives of pesantren in implementing e-money. The study used is a descriptive qualitative method based on observation, interviews. The results of this study concluded that Islamic boarding schools also have the ability to implement e-money transactions as a payment medium by utilizing technology to support the smooth running of Islamic boarding school activities towards a more optimal direction. The goal is to improve pesantren customer service towards a safer and more comfortable direction, create a cahsless society environment, and paperless offices that can streamline data. The impact of this research is the hope that more and more pesantren will implement non-cash transactions to their students, as one of the positive responses of pesantren in the development of the times so that they can prepare a generation of highly competitive nations with the provision of strong religious understanding, intellectual intelligence and able to understand and manage information and communication technology.